511 DO ORAL NUTRITIONAL SUPPLEMENTS IMPROVE QUALITY OF LIFE IN THE FRAIL ELDERLY- A SYSTEMATIC REVIEW. (14th June 2021) - Ryan, C; Hynd, I
Abstract: Background: Oral nutritional supplements (ONS) are regularly used in older frail adults to help reduced oral intake, recovery from acute illness and weight gain. As, many frailer patients have limited life expectancies the priority for treatment should be improving quality of life (QoL). We set out to find if ONS increase QoL in the frail elderly adult. Method: We searched Embase, Medline and OVID databases for using terms for ONS, frail older adults and QoL. The two authors independently reviewed all papers with any dispute was resolved by discussion. Each paper was then reviewed by both authors to extract data and determine bias before collation. Results: The search returned 516 papers. Each paper was briefly reviewed to check for relevance leaving 65 papers for detailed review of which 8 papers were included. Two systematic reviews were included. One was unable to draw conclusions from the 3 papers (out of 17) that included QoL as the graded evidence was too poor. The other showed no impact on QoL (in the 2 out of 12 papers that included QoL) in patients post hip fracture receiving ONS. One paper interviewed frail elderly patients about the perceived benefits of their ONS. Nursing home residents perceived that ONS improved their ability to see family which was inferred as improving QoL. Three papers assessed ONS in conjunction with physical exercise. Two showed an improvement in quality of life in the ONS group despite controls also receiving a physical exercise programme. Two papers assessed the impact of ONS on patients discharged from hospital and those chronically unwell- neither showed any difference in QoL. Discussion: Quality of life has been a neglected area of study when assessing the impact of ONS on frail elderly patients. When used in conjunction with physical exercise it seems to have a positive effect.